ANALYSIS OF SCALOGRAM AND CENTRALITY IN LABUHAN BATU REGENCY: IMPLICATIONS FOR SERVICE FACILITY DISTRIBUTION - Muhammad Najmul Fahmi; Meilinda Suriani Harefa; Darwin Parlaungan Lubis; Sendi Permana (USN Kolaka, 2025)
Spatial analysis is important for understanding how service facilities are distributed in a region and identifying key locations within that area. This study examines the layout of service facilities and trends in centrality in Labuhan Batu Regency, employing the Scalogram Method in conjunction with Centrality Analysis. The Scalogram Method evaluates the variations and access levels of service facilities to classify sub-districts according to their hierarchical positions, while Centrality Analysis determines important areas that greatly influence spatial dynamics and the delivery of services. The findings show significant variations in the ranking of services and regional importance, with Rantau Utara recognized as the primary service center, attaining the top scores in both the scalogram and centrality evaluations. In addition, Bilah Hulu and Rantau Selatan demonstrate significant spatial impact, enhancing their functions as secondary service hubs. In comparison, areas such as Panai Hilir, Panai Hulu, and Pangkatan are rated lower in terms of service order and importance, highlighting the need for enhanced infrastructure and improved distribution of services. The classification of centrality into four distinct categories creates an organized method for comprehending spatial impact, highlighting the distinctions between primary service centers and less central areas. These results emphasize the importance of fair regional development, indicating the need for specific policies to increase access to services, strengthen connections between regions, and promote balanced infrastructure development. By combining findings from the Scalogram and Centrality Analysis, this study provides valuable viewpoints for regional planning, presenting essential suggestions to improve service distribution and promote spatial equality in Labuhan Batu Regency